2020
DOI: 10.1130/g47976.1
|View full text |Cite
|
Sign up to set email alerts
|

Autogenic delta progradation during sea-level rise within incised valleys

Abstract: Using a simple conceptual model of incised-valley evolution, we show that the classic sequence stratigraphic phenomenon of bayhead deltaic systems can be generated by purely autogenic progradation during the late stage of valley flooding. This transient “auto-advance” event occurs under conditions of constant base-level rise and sediment supply, and it results from a strong decrease of in-valley accommodation as base level rises toward the valley apex. We present a laboratory experiment to illustrate the plaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In this work, we provide evidence that an allogenic sea level forcing influences both surface processes and subsurface form. This finding is consistent with prior studies on the subject, which showed that steady SLR (e.g., Feng et al., 2019; Finotello et al., 2019; Guerit et al., 2021; Liang, Van Dyk, & Passalacqua, 2016; Martin, Sheets, et al., 2009) and base level cycles (e.g., Hajek et al., 2014; Kim et al., 2006; Koss et al., 1994; van Heijst & Postmal, 2001) impact both surface processes and the resulting stratigraphy. Uniquely, here, we focus on SLR acceleration by testing the impact that different future sea level trajectories may have on deltaic landscapes.…”
Section: Discussionsupporting
confidence: 93%
“…In this work, we provide evidence that an allogenic sea level forcing influences both surface processes and subsurface form. This finding is consistent with prior studies on the subject, which showed that steady SLR (e.g., Feng et al., 2019; Finotello et al., 2019; Guerit et al., 2021; Liang, Van Dyk, & Passalacqua, 2016; Martin, Sheets, et al., 2009) and base level cycles (e.g., Hajek et al., 2014; Kim et al., 2006; Koss et al., 1994; van Heijst & Postmal, 2001) impact both surface processes and the resulting stratigraphy. Uniquely, here, we focus on SLR acceleration by testing the impact that different future sea level trajectories may have on deltaic landscapes.…”
Section: Discussionsupporting
confidence: 93%
“…So, both deltas migrate towards their respective sediment sources, which are at opposite ends of the estuary. Such retreating deltas are also observed in experimental studies of fluvial deltas with sealevel rise (Guerit et al, 2021;Muto & Steel, 2001). There, the back-stepping of delta lobes is attributed to avulsions instead of allogenic changes in sediment supply or accommodation creation.…”
Section: Flood-tidal Delta Aggradation and Retreatmentioning
confidence: 66%
“…For a valley that deepens and widens in the seaward direction (Fig. 1E), the model is the same as that presented in Guerit et al (2020). Hence, it is only briefly summarized here.…”
Section: Shoreline Migration Patterns For Complex Valley Geometriesmentioning
confidence: 99%
“…During stage 3, with a further increase in the sea level, A decreases gradually to the point where A is smaller than S, which induces the resumption of progradation, albeit in the overall context of sea-level rise. This condition at stage 3 is termed 'auto-advance' by Guerit et al (2020).…”
Section: Shoreline Migration Patterns For Complex Valley Geometriesmentioning
confidence: 99%
See 1 more Smart Citation